Faktor-Faktor yang Mempengaruhi Penyelenggaraan Kartu Identitas Berobat (KIB) pada Sistem Penomoran Unit di Tempat Pendaftaran Pasien Rawat Jalan RSU Darmayu Ponorogo - Brenda Hapsari Eka Saputri; Ani Rosita; Rumpiati Rumpiati (Politeknik Kesehatan Kemenkes Mamuju, 2019)
Organizing identity card medical treatment (KIB) on unit numbering system has not been suitable Standard Operational Procedure (SOP) old outpatient patient registration. The purpose of this research is to know the factors that affect the organization of the identity card for the medical treatment (KIB) on unit numbering system in place of the outpatient registration RSU Darmayu Ponorogo. The design of this research is a descriptive qualitative approach. The sampling techniques used in saturated and incidental sampling. The population of this entire research officer at the place of registration of the outpatients numbered 7 people and outpatients who visit in April 2018. Method of collecting data using interviews, questionnaires and observation. Data analysis using descriptive analysis. Based on the results of research conducted at RSU Darmayu Ponorogo is a factors that affects the educational qualifications of the officers outpatient registration there has not beengraduates of the medical record, there hasn't been written to build SOP KIB for new patient, facilities and infrastructure are inadequate. RSU DarmayuPonorogo parties expected to evaluate activities of the outpatient registration officers, evaluate SOP patient registration, and add to the completeness of facilities and infrastructure.